Expresión ¬A∧((A∨B)∨(A∨C))
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
¬a∧(a∨b∨c)=¬a∧(b∨c)
¬a∧(b∨c)
Tabla de verdad
+---+---+---+--------+
| a | b | c | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 0 |
+---+---+---+--------+
¬a∧(b∨c)
(b∧¬a)∨(c∧¬a)
Ya está reducido a FNC
¬a∧(b∨c)
(b∧¬a)∨(c∧¬a)